Marketing Potential of Suwar-Suwir Product in The Suwar-Suwir Production Gallery, As Special Souvenir From Jember, Indonesia - Iskandar, Sulhan; Susilo, David Kristian; Prasetiyorini, Pudhak (Golden Ratio of Community Services and Dedication, 2025)
This study analyzes the marketing potential of Suwar-Suwir, a traditional Jember product produced by the Candiber Suwar-Suwir Gallery in Kresek Village, Jember Regency. This product is a culinary icon made from fermented cassava (tape singkong) with a distinctive flavor. The research employs a descriptive qualitative approach using a case study method, with data collected through observation, interviews, and documentation. The findings reveal that the current marketing strategy incorporates the marketing mix concept (4P: product, price, place, and promotion) and digital marketing via social media and e-commerce platforms. However, digital media utilization remains suboptimal due to limitations in human resource capacity. Candiber Suwar-Suwir holds significant potential to expand into the national market through enhanced digital marketing strategies, human resource development, product innovation, and collaborations with the tourism sector and modern retail industries. The study recommends implementing aggressive digital promotion strategies and scaling production capacity to meet broader market demands.